Antibacterial in vitro screening of Helminthostachys zeylanica (L.) Hook. root extracts - Monika Kerry Army; Rohimatul Khodijah; Yuli Haryani; Hilwan Yuda Teruna; Rudi Hendra (GarVal Editorial Ltda., 2023)
Context: Helminthostachys zeylanica (L.) Hook. has been used as a traditional medicine plant to treat diabetic mellitus and various infectious in China, Malaysia, and Indonesia. Aims: To determine the antibacterial activity of H. zeylanica root extracts against various pathogenic bacteria. Methods: The extraction was carried out by maceration of fresh roots using methanol, then partitioned to obtain extracts of n-hexane, dichloromethane, ethyl acetate, and water. The extracts were tested for antibacterial activity using the agar diffusion method, minimal inhibition concentration (MIC), and minimal bactericidal concentration (MBC). Results: Dichloromethane and ethyl acetate extracts showed inhibitory activity against Bacillus subtilis ATCC 1965, Staphylococcus aureus ATCC 6538, B. cereus ATCC 10876, Vibrio parahaemolyticus ATCC 17802, V. alginolyticus ATCC 17749, Listeria monocytogenes ATCC 7644, and Salmonella typhimurium ATCC 142028. The MIC value of dichloromethane extract against these bacteria was 125-500 µg/mL, while the ethyl acetate extract was 500 µg/mL. Furthermore, the MBC for dichloromethane against bacteria B. subtilis and V. parahaemolyticus were 250 µg/mL. Conclusions: The study demonstrated the in vitro antibacterial potential of the species extracts against pathogenic bacteria. The dichloromethane and ethyl acetate extracts showed the most significant inhibitory activity, suggesting that this plant could be a potential source for developing new antimicrobial agents. Further research is needed to identify the active compounds responsible for the observed effects.